The Effect of Emotional Intelligence and Financial Compensation on Work Motivation and Employee Performance - Fauzan, Rizky (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to examine and analyze the effect of emotional intelligence, financial compensation on employee performance through work motivation as a mediation at PT Anzon Autoplaza. This study is a causal associative research and uses a questionnaire distributed to employees of PT Anzon Autoplaza in Pontianak City. The test method that will be used is path analysis test. The sample used is 78 respondents of sales employees. The data analysis technique used simple linear regression analysis with the help of SPSS 16. The results is Emotional Intelligence and Financial Compensation had an effect on work motivation in sales employees. However, Emotional Intelligence, Financial Compensation, and Work Motivation have no effect on employee performance. Emotional Intelligence, and Financial Compensation also have no effect on Employee Performance through Work Motivation as a Mediation.